SENTRA KULINER SEBAGAI PENUNJANG KEBERLANJUTAN WISATA SUNGAI KALIMAS SURABAYA - Suryo Adinugroho; Alexander Mario Retto Djong; Kristian Faskahariyanto; Truli Nugroho (POLITEKNIK LP3I JAKARTA, 2025)
This study aims to identify the contribution of culinary centers to the sustainability of tourism in the area, which includes economic, social, and environmental dimensions. The research method used is a mixed-method approach with data collection through observation, in-depth interviews, and surveys of visitors and culinary business actors around the Kalimas River. The results of the study indicate that the existence of culinary centers around the Kalimas River in Surabaya has a positive impact, such as increasing income for local business actors, creating jobs, and strengthening local cultural identity through the presentation of typical foods. However, this study also found challenges in waste management and maintaining environmental quality that must be overcome to support the sustainability of tourist destinations.